Habitar a terra: cartografia de um encontro entre conceitos do design estratégico para a sustentabilidade de Ezio Manzini, da ecosofia de Gilles Deleuze e Félix Guattari, e da ecologia cognitiva de Pierre Lévy - Pastori, Douglas Onzi (Universidade do Vale do Rio dos Sinos, 2010)
Questioning the ecological effects, not only from environmental view but also from social and mental of human habitation in a planet that passes through deep transformation, this research explores the area of Strategic Design for Sustainability, in order to map its most relevant concepts and get from its manifest discourse the underlying content that engenders them, emphasizing a special attention to the structured questions and to the political motives that formalize them. For this, we selected part of a special author?s research, the Italian teacher Ezio Manzini, as the main concept synthesizer of this new research area, as well as an area of some speakers who were privileged by their connection with the used method - schizoanalitic cartography - and also by the nearness with the ecological thematic line: the Ecosophy of Gilles Deleuze and Félix Guattari and the Cognitive Ecology of Pierre Lévy. Summing up, we proposed some changes in the concept web that was mapped with the objective of singularizing the theoretical-project course of the Strategic Design's new area for Sustainability.
Keywords: Design estratégico; Sustentabilidade; Ecodesign; Ecologia; Ecosofia; Cartografia; Strategic design; Sustainability; Ecology; Ecosophy; Cartography; ACCNPQ::Ciências Sociais Aplicadas::Desenho Industrial